2005
DOI: 10.1152/jn.00777.2004
|View full text |Cite
|
Sign up to set email alerts
|

Role of Mossy Fiber Sprouting and Mossy Cell Loss in Hyperexcitability: A Network Model of the Dentate Gyrus Incorporating Cell Types and Axonal Topography

Abstract: Mossy cell loss and mossy fiber sprouting are two characteristic consequences of repeated seizures and head trauma. However, their precise contributions to the hyperexcitable state are not well understood. Because it is difficult, and frequently impossible, to independently examine using experimental techniques whether it is the loss of mossy cells or the sprouting of mossy fibers that leads to dentate hyperexcitability, we built a biophysically realistic and anatomically representative computational model of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
372
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 251 publications
(384 citation statements)
references
References 91 publications
9
372
0
Order By: Relevance
“…In response to a simulated perforant path input to 5,000 GCs (10%), 50 basket cells (10%), and 10 mossy cells (1.3%) (referred to as ''10% stimulation''), the control network (which, as described above, includes a simulated moderate injury resulting in cell loss and mossy-fiber sprouting) exhibited limited hyperexcitability (Fig. 1C), in agreement with previous findings (11,21). Activity spread to the entire network by 83.67 Ϯ 1.07 ms, and GC firing duration was 207.78 Ϯ 10.35 ms.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…In response to a simulated perforant path input to 5,000 GCs (10%), 50 basket cells (10%), and 10 mossy cells (1.3%) (referred to as ''10% stimulation''), the control network (which, as described above, includes a simulated moderate injury resulting in cell loss and mossy-fiber sprouting) exhibited limited hyperexcitability (Fig. 1C), in agreement with previous findings (11,21). Activity spread to the entire network by 83.67 Ϯ 1.07 ms, and GC firing duration was 207.78 Ϯ 10.35 ms.…”
Section: Resultssupporting
confidence: 90%
“…Although the mechanisms of activity termination were not explicitly investigated, they are likely to include synaptic inhibition from basket and HIPP cells, activation of calcium and voltagedependent potassium conductances, and the intrinsic properties of the granule cells themselves that have a ''default'' silent state (21). Importantly, these mechanisms do not differ between the control and experimental networks.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CA3 transplant-mediated restitution of the disrupted circuitry is also associated with a dramatic inhibition of the aberrant mossy fiber sprouting into the dentate inner molecular layer (Shetty et al, 2005). Because sprouted mossy fibers make excitatory connections with the dendrites of granule cells and dentate gyrus with aberrant mossy fiber sprouting has increased seizure susceptibility (Mathern et al, 1996(Mathern et al, , 1998Sutula, 2002;Nadler, 2003;Santhakumar et al, 2005), it is likely that suppression of the aberrant mossy fiber sprouting mediated by fetal CA3 cell grafts contributes to decreased hyperexcitability in the dentate gyrus of the injured hippocampus. Second, studies have suggested that neural transplant mediated functional recovery after injury to discrete brain regions requires specific axon growth from transplanted neurons into both local and distant host neurons leading to at least partial restitution of the damaged circuitry (Wictorin, 1992;Dunnett, 1995;Dunnett et al, 1997;Isacson and Deacon, 1997;Isacson, 2003;Turner and Shetty, 2003;Ferrari et al, 2006).…”
Section: Potential Mechanisms Of Calbindin Restoration In the Injuredmentioning
confidence: 99%
“…Contributions of specific neuronal populations have been observed to be variable, and certain well-connected networks appear to play a greater role in the ini-tiation and progression of large-scale network events (Morgan and Soltesz 2008;Keller et al 2010;Sabolek et al 2012). In addition, work from high-level network theory and data-driven computational studies have modeled how altered neural circuit connections can trigger seizure activity (Santhakumar et al 2005;Dyhrfjeld-Johnsen et al 2007;Morgan and Soltesz 2008;Bullmore and Sporns 2009). These experimental breakthroughs and theoretical and computational models have been important in advancing our knowledge of how seizures initiate and propagate through the brain.…”
mentioning
confidence: 99%